THE EFFECT OF TAMARIND (TAMARINDUS INDICA) LEAF EXTRACT OINTMENT IN CONTROLLING THE GROWTH OF THE BACTERIA PROPIONIBACTERIUM ACNES THAT TRIGGERS ACNE - Hasna Azzahra; Fianicha Shalihah; Indah Nurlita Trisnawati; Siti Aeniah; Lintang Prima Cahyani; Alanindra Saputra (Universitas Medan Area, 2022)
Tamarind (Tamarindus indica) is a versatile plant, findable in Indonesia (Java, Bali, North Sumatra, West Kalimantan, and South Sulawesi). The leaves are green to brown, round, 1-2.5 cm long and 4-8 mm wide, rounded tips, rounded base of blades, and flat edges. The content contained in tamarind leaves such as flavonoids, tannins, saponins, and alkaloids is believed to inhibit Propionibacterium acnes activity. This study aims to determine the effect of tamarind leaf extract ointment in controlling the growth of the bacteria Propionibacterium acnes that triggers acne. This study applied a Completely Randomized Design with 96% ethanol maceration method. Propionibacterium acnes was evidenced by the inhibition zone formed. The diameter of the inhibition zone of the 25% ointment was 1.235 cm, the 30% concentration was 1.385 cm, the 35% concentration was 1,680 cm, and the ointment base was 0 cm. The ANOVA test showed a significant value of 0.000<0.05, so there was a significant difference between the inhibition zone and the 95% confidence level. The results of Post Hoc test were P<0.05, meaning that there was a significant difference between the bases with formulas 1, 2, and 3. Thus, tamarind leaf extract ointment had a strong inhibitory effect on Propionibacterium acnes.